The Murine Double-Stranded RNA-Dependent Protein Kinase PKR Is Required for Resistance to Vesicular Stomatitis Virus - Stojdl, David F. (American Society for Microbiology, 2000)
Interferon (IFN)-induced antiviral responses are mediated through a variety of proteins, including the double-stranded RNA-dependent protein kinase PKR. Here we show that fibroblasts derived from PKR(−/−) mice are more permissive for vesicular stomatitis virus (VSV) infection than are wild-type fibroblasts and demonstrate a deficiency in alpha/beta-IFN-mediated protection. We further show that mice lacking PKR are extremely susceptible to intranasal VSV infection, succumbing within days after instillation with as few as 50 infectious viral particles. Again, alpha/beta-IFN was unable to rescue PKR(−/−) mice from VSV infection. Surprisingly, intranasally infected PKR(−/−) mice died not from pathology of the central nervous system but rather from acute infection of the respiratory tract, demonstrating high virus titers in the lungs compared to similarly infected wild-type animals. These results confirm the role of PKR as the major component of IFN-mediated resistance to VSV infection. Since previous reports have shown PKR to be nonessential for survival in animals challenged with encephalomyocarditis virus, influenza virus, and vaccinia virus (N. Abraham et al., J. Biol. Chem. 274:5953–5962, 1999; Y. Yang et al., EMBO J. 14:6095–6106, 1995), our findings serve to highlight the premise that host dependence on the various mediators of IFN-induced antiviral defenses is pathogen specific.